The ethical problems of abortion in the Encyclical Evangelium Vitae. - Ciccone, Lino (Medicina e Morale, 1995)
The author proposes to point out what the Encyclical Evangelium Vitae (EV) adds to the already considerably numerous moral teachings on abortion provided by the Catholic Church. After briefly mentioning some new aspects which, in a certain sense, are marginai compared to the main point of the doctrine, the author describes how EV deals with the ethical problem brought up by the law on abortion, starting with the evaluation of these kinds of law and of the countries that passes it and EV formulates this evaluation in particularly severe terms, but with good reason. The solution to two of the most serious and complex problems in EV, which are a result of the Iegalization of abortion, is given: conscientious objectors and new forms that cooperation with performing abortion assumes. But EV also presents significant new elements on abortion itself, and these are briefly underlined. Finally the author demostrates the intense passionale love for man that traspires from EV which, if read too quickly or superficially, risks appearing as a series ofsevere, coldly formulated condemnations.